2015
DOI: 10.1002/masy.201550308
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organoclay on Curing Characteristic, Mechanical Properties, Swelling and Morphology of Natural Rubber/Organoclay Nanocomposites

Abstract: Summary: Rubber nanocomposites based on the natural rubber (NR) and organically modified montmorillonite (OMMT) were prepared by melt intercalation technique using a laboratory open mill followed by compression molding. Organically modified organoclays with different d-spacing were added to the natural rubber matrix to examine the influence of d-spacing of organoclay on morphology, curing characteristic and mechanical property of nanocomposite. The characterizations were carried out by means of X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…The tensile strength of control NR is 6.7 MPa which is close to previous report using SIR 20 as binder [28]. The strength is also close to another study using different NR [29], but lower than others [30,31]that may be due to differences on NR type and formulations.…”
Section: Ftir Analysissupporting
confidence: 75%
“…The tensile strength of control NR is 6.7 MPa which is close to previous report using SIR 20 as binder [28]. The strength is also close to another study using different NR [29], but lower than others [30,31]that may be due to differences on NR type and formulations.…”
Section: Ftir Analysissupporting
confidence: 75%
“…It was reported that the exfoliation would also support for an enhancement in tensile strength . However, in another study, it was showed that high exfoliation of organoclay in rubber caused inhibition of strain‐induced crystallization and thereby to increase modulus while reducing tensile strength …”
Section: Resultsmentioning
confidence: 99%